2009
DOI: 10.1021/es901706j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Silver Nanoparticles with Pseudomonas putida Biofilms

Abstract: Silver nanoparticles (Ag NPs) may present a risk to the environment due to their expected toxicity and wide exposure. The interactions between Ag NPs and laboratory-grown Pseudomonas putida biofilms were investigated under a range of environmentally relevant conditions (pH 6 and 7.5; presence and absence of Suwannee River fulvic acid (SRFA)) over 4 days. In the absence of SRFA, there was extensive sloughing of the biofilm bacteria into suspension implying NP-bacterial interactions and potential effects on NP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(146 citation statements)
references
References 29 publications
3
135
3
1
Order By: Relevance
“…The diameter of inhibitory zones ranged from 7.66 to 38.33 mm for AgNO 3 and AgNPs treatments, respectively (Table 3; Figure 5). The highest inhibitory effect was observed in treatment with 10 mg of AgNO 3 [67][68][69][70][71] In addition, biosynthesized Ag-NPs isolated from Citrullus colocynthis callus and Phyllanthus amarus extracts exhibited tremendous antibacterial activity against E. coli, P. aeruginosa, and P. vulgaris. 5,52 Both the concentrations of Ag-NPs (5 and 10 mg/mL) did not show any inhibitory activity against S. marcescens and positive strains like B. cereus 72 reported that Ag-NPs possessed antifungal properties because extracellular synthesis of NP helps trap metal ions on the cell surface and helps reduce ions in the presence of enzymes.…”
Section: In Vitro Antimicrobial Activity Disk Diffusion Antibacterialmentioning
confidence: 99%
“…The diameter of inhibitory zones ranged from 7.66 to 38.33 mm for AgNO 3 and AgNPs treatments, respectively (Table 3; Figure 5). The highest inhibitory effect was observed in treatment with 10 mg of AgNO 3 [67][68][69][70][71] In addition, biosynthesized Ag-NPs isolated from Citrullus colocynthis callus and Phyllanthus amarus extracts exhibited tremendous antibacterial activity against E. coli, P. aeruginosa, and P. vulgaris. 5,52 Both the concentrations of Ag-NPs (5 and 10 mg/mL) did not show any inhibitory activity against S. marcescens and positive strains like B. cereus 72 reported that Ag-NPs possessed antifungal properties because extracellular synthesis of NP helps trap metal ions on the cell surface and helps reduce ions in the presence of enzymes.…”
Section: In Vitro Antimicrobial Activity Disk Diffusion Antibacterialmentioning
confidence: 99%
“…The results suggested that biofilms are impacted by the treatment with AgNPs. The nanoparticles analyzed in the study were of quite large dimensions (over 60 nm) [80]. One of the first reports on the antibiotic effect of AgNPs on P. aeruginosa and S. epidermidis, and their effect on biofilm formation, was produced by Kalishwaralal et al [81].…”
Section: Agnps Antibiofilm Activitymentioning
confidence: 99%
“…The results suggested that biofilms are impacted by the treatment with NPs. The nanoparticles analyzed in the study were ofquite large dimensions (over 60 nm) (80). One of the first reports on the antibiotic effect of NPs on P. aeruginosa and S. epidermidis, and their effect on biofilm formation, was produced by Kalishwaralal et al2010., (81).…”
Section: The Antibiofilm Activity Of Nanoparticlesmentioning
confidence: 99%